Kontrola jakości działalności administracyjnej przedsiębiorstwa produkcyjnego - Gubicz-Stachowiak, Dorota (The quality control in the administration activity, 2006)
The term “Quality” is very important for companies. Quality in management and administration is a big step for a development. The article describes methods and instruments which are usefull in quality control. The process of control should be carried out systematically by both internal and independent external controllers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 135-142